(untitled) (Resunga Journal रेसुङ्गा जर्नल, 2024)
This study examines the effects of non-performing loan and operational efficiency on profitability of Nepalese commercial banks. Return on asset and return on equity are selected as the dependent variables. Similarly, loan to deposit ratio, capital adequacy, loan loss provision, non-performing loan, operating income and operating expenses are selected as the independent variables. This study is based on secondary data of 15 commercial banks with 105 observations for the study period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank(NRB), annual reports of the selected commercial banks and reports published by Ministry of Finance. The correlation coefficients and regression models are estimated to test the significance and importance of loan to deposit ratio, capital adequacy ratio, loan loss provision, and non-performing loan, operating income and operating expenses on the profitability of Nepalese commercial banks. The study showed that that loan loss provision ratio, non-performing loan ratio and capital adequacy ratio are the positive impact return on assets (ROA). It indicates that higher the loan loss provision ratio, non-performing loan ratio and capital adequacy ratio, higher would be the bank return on assets (ROA) of commercial banks in Nepal. Similarly, the study also shows that loan to deposit ratio, operating income ratio and operating expenses ratio have a negative impact on return on assets (ROA). It indicates that higher the loan to deposit ratio, operating income ratio and operating expenses ratio lower would be the return on assets of Nepalese commercial banks.